Pengaruh Pengaruh Soft Skill dan Hard Skil Mahasiswa Terhadap Kesiapan Kerja di Era Revolusi Industri 4.0 - Fadia Kasim; Andi Indriani Ibrahim; Syahir Natsir; Buntuang, Pricylia Chintya Dewi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the influence of soft skills and hard skills on students’ work readiness in the Industrial Revolution 4.0 era. Using a quantitative approach, data were collected from 184 Management students at Tadulako University and analyzed through bootstrapping-based multiple regression. The findings reveal that soft skills and hard skills have positive and significant effects on work readiness, both partially and simultaneously, with a contribution of 43.5%. Hard skills are the more dominant predictor. These results suggest that universities should strengthen both soft and hard skills through integrated curriculum development. Keywords: Soft Skills; Hard Skills; Work Readiness; Industrial Revolution 4.0